Holistic Marketing 3.0: Menuju Organisasi Spiritual - Premananto, Gancar Candra (Universitas Muhammadiyah Surakarta, 2014)
Holistic Marketing is become new mantra for marketer in this 21 century. The concept builds on 4 pillars which are integrated marketing, internal marketing, performance marketing and relationship marketing. The point of that concept is about the important things is to make relationship to everybody and to every stakeholders. The concepts still on development process by Kotler & Keller. This conceptual article proposed that Holistic Marketing proposed by Kotler & Keller still discuss about horizontal relationship. It is not include the important relationship that should be building by human, which is relationship to God. Those relationship can make organization can apply the concept of HabluminaLLAH, habluminannas dan rahmatan lil âalamin. The concept proposed as Holistic Marketing 3.0, to make more complete and holistic relationship.